2015
DOI: 10.1111/mec.13168
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diversification associated with ecological specialization in NeotropicalAdelphabutterflies

Abstract: Rapid diversification is often associated with morphological or ecological adaptations that allow organisms to radiate into novel niches. Neotropical Adelpha butterflies, which comprise over 200 species and subspecies, are characterized by extraordinary breadth in host plant use and wing colour patterns compared to their closest relatives. To examine the relationship between phenotypic and species diversification, we reconstructed the phylogenetic history of Adelpha and its temperate sister genus Limenitis usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 99 publications
4
72
2
Order By: Relevance
“…Contrary to this prediction, we found that unpalatable A. iphiclus was attacked significantly less than palatable A. serpa (palatability assumptions based on larval host plant use ;Aiello 1984;Ebel et al 2015), suggesting that A. serpa does not benefit from sharing a convergent wing pattern with A. iphiclus. Contrary to this prediction, we found that unpalatable A. iphiclus was attacked significantly less than palatable A. serpa (palatability assumptions based on larval host plant use ;Aiello 1984;Ebel et al 2015), suggesting that A. serpa does not benefit from sharing a convergent wing pattern with A. iphiclus.…”
Section: Mimicrycontrasting
confidence: 99%
“…Contrary to this prediction, we found that unpalatable A. iphiclus was attacked significantly less than palatable A. serpa (palatability assumptions based on larval host plant use ;Aiello 1984;Ebel et al 2015), suggesting that A. serpa does not benefit from sharing a convergent wing pattern with A. iphiclus. Contrary to this prediction, we found that unpalatable A. iphiclus was attacked significantly less than palatable A. serpa (palatability assumptions based on larval host plant use ;Aiello 1984;Ebel et al 2015), suggesting that A. serpa does not benefit from sharing a convergent wing pattern with A. iphiclus.…”
Section: Mimicrycontrasting
confidence: 99%
“…As a powerful and the most-commonly-used approach, RAD sequencing has limitations. Key among these is the reliance on restriction enzyme digestion in the workflow, which limits the approach to use with vertebrates, or relatively large arthropods, from which a sufficiently-large quantity of DNA can be extracted from individuals (e.g., stickleback fish, [70]; land snails, [74]; butterflies, [76]). NextRAD substitutes transposomes for restriction enzymes, necessitating less DNA per sample and thus allowing the approach to be used with small amounts of DNA [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore important to establish a phylogenetic and ecological framework for recently emerged continental clades that are widespread, species-rich, and ecologically diverse. The study of such recent radiations can ultimately provide further insight into the factors that have shaped macroevolutionary patterns across a continent [10,11,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%